Site selection evaluation of transmission lines in desert areas based on wind-sand physics - Moxian Dai; Moxian Dai; Yanbing Wang; Shu Zhu; Hongchao Dun; Hongchao Dun (Frontiers in Environmental Science, 2025)
With the rapid global expansion of wind and photovoltaic power generation in desert regions, transmission lines selection has become crucial for effective renewable energy delivery. This study develops a new evaluation framework for transmission lines siting in desert environments through wind-blown sand dynamics analysis. Leveraging global desert distribution data and ECMWF Reanalysis v5 Land(ERA5-Land) wind field data (2001 2020), we quantified 20-year sand drift potential patterns and established a comprehensive scoring system for infrastructure suitability assessment. The study findings reveal that global desert sand movement exhibits distinct spatial distribution patterns. Temporally, all monitored regions demonstrate a continuous intensification of sand drift potential, with South America showing the most rapid growth rate, while Asia and Africa maintain relatively stable patterns. The developed scoring system effectively identifies optimal transmission lines selection through multivariate analysis of aeolian processes. This methodology provides decision-makers with science-based tools for energy infrastructure planning in aeolian-active regions, particularly supporting sustainable development of desert renewable energy projects.